A Comparative Study of Barbed Sutures vs. Conventional Sutures in Laparoscopic Surgery: Efficiency, Infection Rate, Cost, and Handling - Dr. R. Varahini; Dr. J. Sharath Kumar (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Laparoscopic surgery has revolutionized surgical procedures by reducing recovery time and enhancing patient outcomes. Suturing during these procedures remains a critical step that impacts surgical efficiency, infection rates, and overall cost. Barbed sutures, which eliminate the need for knot tying, are proposed as an alternative to conventional sutures. This study aimed to compare barbed sutures with conventional sutures in terms of suturing time, ease of handling, infection rates, and cost in laparoscopic surgeries. Methods: A prospective randomized controlled trial was conducted with 100 patients undergoing elective laparoscopic surgery at Venkateshwara Medical College, Puducherry. Participants were randomly assigned to either the barbed suture group (n=50) or the conventional suture group (n=50). The primary outcomes assessed included suturing time, ease of handling, infection rates, and cost. Statistical analyses were performed using independent t-tests and chi-square tests. Results: The barbed suture group showed a significant reduction in suturing time (9.4 ± 2.1 minutes) compared to the conventional suture group (14.7 ± 3.5 minutes, p<0.001). Handling was rated significantly higher for barbed sutures (4.3/5 vs. 3.2/5). Infection rates were similar in both groups (4% vs. 8%, p=0.43), but costs for barbed sutures were higher (₹1,200 vs. ₹500), though the overall surgical cost was slightly lower in the barbed suture group. Conclusion: Barbed sutures provide significant time savings and ease of handling compared to conventional sutures, with similar infection rates. Despite higher upfront costs, barbed sutures offer improved surgical efficiency and can be considered a beneficial alternative in laparoscopic surgery.